Potensi Penerapan Konsep Ekologi Industri Untuk Mengatasi Limbah Peternakan Dan Pertanian Kelompok Tani - Shafwan Amrullah; Theresia Evila Purwanti Sri Rahayu; Cyrilla Oktaviananda (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2020)
The agriculture and livestock sector is the biggest contributor to environmental damage. Where from the total national sources of greenhouse gases, the agricultural sector accounted for 13.6%. From this data, there needs to be an appropriate design to deal with this problem. One way is to apply the concept of industrial ecology as the best solution to deal with this problem. So that in this study quantitative calculations were carried out to determine the potential application of the concept of industrial ecology in the agriculture and animal husbandry sector in the Tojang Maju 3 Farmer Group located in Masbagik District, East Lombok Regency, West Nusa Tenggara Province. The study was conducted with a quantitative calculation of waste generated by the livestock sector as well as farmer group questions, which then carried out the design process of the industrial ecological model. The results obtained the use of liquid organic fertilizer (POC) in the agricultural sector as much as 280.5 for rice, 37.4 for chilli farming, and 37.4 liters for cabbage farming and the rest as sources of economics. Whereas straw produced by rice farming (57,000 kg) is used as silage in the livestock sector with a demand of 4,957.2 kg. Rice straw is also used in the chilli agriculture sector as mulch with a requirement of 1,140 kg and the rest (50,903 kg) is used as raw material for the production of synthetic gas for energy sources of farmer groups. While the rest of the chilli and cabbage agricultural products are used as raw material for biogas with a mass of around 70,300 kg which is directly utilized by the groups. For cow as much as 5,355 kg is fed to the biogas digester as biogas for the consumption of farmer groups, with a gas potential of 535.5 m3.